Manufacturer carterls and resale price maintenance - Matthias Hunold; Johannes Muthers (Johannes Kepler University of Linz, Department of Economics, 2021)
In a model with manufacturer and retailer competition, we show that RPM facilitates manufacturer cartels when retailers have an outside option to selling the manufacturer's product. Because retailers have an effective outside option, the manufacturer can only ensure contract acceptance by leaving a sufficient margin to the retailers. This restricts the wholesale price level even when manufacturers collude. In this context, collusion can only become profitable for manufacturers if they use resale price maintenance. We thus provide a novel theory of harm for resale price maintenance when manufacturers collude and illustrate the fit of this theory in competition policy cases.
Keywords: D43; K21; K42; L41; L42; L81; 330; resale price maintenance; collusion; retailing